FACTS-IR: Fairness, Accountability, Confidentiality, Transparency, and Safety in Information Retrieval - Olteanu, Alexandra; Garcia-Gathright, Jean; Rijke, Maarten de; Ekstrand, Michael D. (ACM SIGIR Forum, 2019)
The purpose of the SIGIR 2019 workshop on Fairness, Accountability, Confidentiality, Transparency, and Safety (FACTS-IR) was to explore challenges in responsible information retrieval system development and deployment. To this end, the workshop aimed to crowdsource from the larger SIGIR community and draft an actionable research agenda on five key dimensions of responsible information retrieval: fairness, accountability, confidentiality, transparency, and safety. Such an agenda can guide others in the community that are interested in pursuing FACTS-IR research, as well as inform potential funders about relevant research avenues. The workshop brought together a diverse set of researchers and practitioners interested in contributing to the development of a technical research agenda for responsible information retrieval.